Integration of Environmental and Economic Aspects in Green GRDP Calculation on the Industrial Sector in West Bandung District, Indonesia - Falatehan, Faroby; Bahtiar, Rizal (European Journal of Sustainable Development, 2019)
West Bandung Regency is a developing district in West Java, Indonesia. As a developing city, the industrial sector is one sector that has a large share of Regional GDP in this district, which is 39%. On the other hand, based on the concept of sustainable development, the calculation of Regional GDP or Gross Regional Domestic Product (GRDP) has not paid attention to aspects of resources depletion and environmental degradation. Therefore, Regional GDP is difficult to measure the business benefits of the industrial sector in the concept of sustainable development. This paper introduces concept of green Regional GDP and its contribution to regional income. This paper analyzes the value of depleted resources and degraded environments in the region, from 2015 to 2017. Resource depletion is focused on depletion of water resources. Whereas the degradation that occurs is focused on congestion and damage to water resources due to industrial waste. The industrial sector Green Regional GDP has resulted in a reduction in Regional GDP of 1.17% in 2015, 1.12% in 2016 and 1.06% in 2017. Therefore, an appropriate policy is needed in overcoming this problem, especially reducing environmental damage, namely reducing congestion and reducing environmental pollution in order to achieve sustainable development. Keywords: Sustainable development, Depletion, Degradation, Water, Congestion, Damage